Odraščanje z oviro - Ule, Mirjana (Socialno delo, 2014)
The article discusses the features of growing up with disability, the crises and overcoming of these crises, the role of significant others, the educational transitions, and the experience with institutions and experts. It is based on the analysis of the results of qualitative research of students with disabilities. A biographical approach has been used. These are the narratives about how a vital life experience can strengthen the individual, provided that they have a supportive living environment and empathic responses of the institutional environment that is supported by appropriate systemic solutions. Judging from the statements of students, the reason for their successful biographies is that they have been accepted by their familiesand have received the proper level of incentives and requirements. That has strengthened them in the way that they were also able to cope with identity crises, the crises of the transitions to adulthood, and with occasional negative reactions of the institutions.
Keywords: destandardizacija; izbirne bibliografije; normalizacija hendikepa; prehodi; student; študenti; osebe z ovirami; odraščanje; življenjski poteki